Dual-source dual-power electrospinning and characteristics of multifunctional scaffolds for bone tissue engineering - Wang, Chong (Springer US, 2012)
Electrospun tissue engineering scaffolds are attractive due to their distinctive advantages over other types of scaffolds. As both osteoinductivity and osteoconductivity play crucial roles in bone tissue engineering, scaffolds possessing both properties are desirable. In this investigation, novel bicomponent scaffolds were constructed via dual-source dual-power electrospinning (DSDPES). One scaffold component was emulsion electrospun poly(d,l-lactic acid) (PDLLA) nanofibers containing recombinant human bone morphogenetic protein (rhBMP-2), and the other scaffold component was electrospun calcium phosphate (Ca–P) particle/poly(lactic-co-glycolic acid) (PLGA) nanocomposite fibers. The mass ratio of rhBMP-2/PDLLA fibers to Ca–P/PLGA fibers in bicomponent scaffolds could be controlled in the DSDPES process by adjusting the number of syringes used to supply solutions for electrospinning. Through process optimization, both types of fibers could be evenly distributed in bicomponent scaffolds. The structure and properties of each type of fibers in the scaffolds were studied. The morphological and structural properties and wettability of scaffolds were assessed. The effects of emulsion composition for rhBMP-2/PDLLA fibers and mass ratio of fibrous components in bicomponent scaffolds on in vitro release of rhBMP-2 from scaffolds were investigated. In vitro degradation of scaffolds was also studied by monitoring their morphological changes, weight losses and decreases in average molecular weight of fiber matrix polymers.